Shifting Root Strategies: Impacts of Forest Conversion on Fine Root Traits in Monoculture Systems - Susilawati, Susi; Sulistijorini, Sulistijorini; Samhita, Sasya; Triadiati, Triadiati (Bogor Agricultural University, Indonesia, 2026)
The intensification of land-use from natural forests to monoculture systems such as rubber and oil palm plantations alters soil structure and resource availability, thereby affecting fine root acquisition strategies. This study assessed the impact of land-use intensification on fine root morphology, water content, and acquisition strategies across different land-use types. Fine root samples were collected from four systems: natural forest, jungle rubber, rubber, and oil palm plantations (five plots per system). Fine roots were classified into absorptive (first–third order) and transportive (fourth–fifth order), and traits were analyzed using WinRHIZO Pro 2020a. The results showed a decline in absorptive root length along the intensification gradient, with oil palm significantly shorter than forest and jungle rubber. In contrast, root length per area (RLA) was higher in the forest than in rubber plantations. Absorptive root tip length was significantly greater in oil palm compared to rubber. Transportive root length also declined, with significant differences only between oil palm and jungle rubber. Fine root diameter (FRD) and root tissue density (RTD) tended to increase, while specific root length (SRL) and specific root area (SRA) tended to decrease in absorptive roots. In transportive roots, SRL was inconsistent, and SRA remained stable. Water content tended to decrease in absorptive roots but remained relatively stable in transportive roots.